Caring for health-care workers. Experience with a psychological support program for nurses working in Internal Medicine - Elena Albertazzi; Mauro Campanini; Giuseppina Ferrotti; Flavio Bobbio; Giuliana Ziliotto (Italian Journal of Medicine, 2012)
Introduction Nurses working in an Internal Medicine ward must have very specific training and aptitude. Dealing with different types of patients with widely varying ages and different medical issues requires flexibility in managing emergencies and in choosing between various professional interventions, as well as strong communication skills. Because of this variety, the workload is perceived as being particularly heavy. Materials and methods The article describes the intervention of a psychologist in support of the nursing staff of an Internal Medicine ward. The intervention was prompted by findings of high staff turnover. The work began with an analysis of the group dynamics in the nursing team, and the psychologist's action was based on a group approach. In this way, specific problems of the group were solved through the instrument of the group itself, which became the true promoter of change. Results Nurses worked to recognize their professional identity and to strengthen their self-esteem, and this changed their perception of their workload. The team also became more aware of its individual and group resources. These changes decreased staff turnover and reduced arguments between the nurses themselves and between the nurses and patients’ relatives. Discussion The nursing team become more solid and better organized. It dealt with emotional problems and has become more receptive to changes in the way the work is organized.